2017
DOI: 10.1016/j.visres.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the spatial selectivity of the duration after-effect

Abstract: a b s t r a c tAdaptation to the duration of a visual stimulus causes the perceived duration of a subsequently presented stimulus with a slightly different duration to be skewed away from the adapted duration. This pattern of repulsion following adaptation is similar to that observed for other visual properties, such as orientation, and is considered evidence for the involvement of duration-selective mechanisms in duration encoding. Here, we investigated whether the encoding of duration -by duration-selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 80 publications
(128 reference statements)
7
28
0
Order By: Relevance
“…Since we found that the DAE reflected the attended duration and not the unattended duration (a 100% relative contribution of attended durations), our results support the notion that duration is a complex feature encoded by mechanisms located at higher-level areas of the processing hierarchy. This conclusion is in line with recent studies demonstrating low spatial selectivity of the duration after-effect 24 , 38 . This finding indicate that duration-selective neurons possess relatively large receptive fields, again suggesting a locus in higher-level areas of the processing hierarchy 24 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Since we found that the DAE reflected the attended duration and not the unattended duration (a 100% relative contribution of attended durations), our results support the notion that duration is a complex feature encoded by mechanisms located at higher-level areas of the processing hierarchy. This conclusion is in line with recent studies demonstrating low spatial selectivity of the duration after-effect 24 , 38 . This finding indicate that duration-selective neurons possess relatively large receptive fields, again suggesting a locus in higher-level areas of the processing hierarchy 24 .…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion is in line with recent studies demonstrating low spatial selectivity of the duration after-effect 24 , 38 . This finding indicate that duration-selective neurons possess relatively large receptive fields, again suggesting a locus in higher-level areas of the processing hierarchy 24 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Even brief adaptation to a visual numerosity changes the perception of a subsequently viewed numerosity at the same location Castaldi, Aagten-Murphy, Tosetti, Burr, & Morrone, 2016). Likewise, time is also susceptible to adaptation, with adaptation to a previous duration influencing the perception of a subsequently presented duration (Becker & Rasmussen, 2007;Heron et al, 2012;Heron, Hotchkiss, Aaen-Stockdale, Roach, & Whitaker, 2013;Johnston, Arnold, & Nishida, 2006;Li, Chen, Xiao, Liu, & Huang, 2017;Maarseveen, Hogendoorn, Verstraten, & Paffen, 2017;Magnussen & Johnsen, 1986;Shima, Murai, Hashimoto, & Yotsumoto, 2016).…”
Section: Introductionmentioning
confidence: 99%